EFFECTIVITY OF SELECTING BALOXAVIR AS AN ALTERNATIVE TREATMENT FOR INFLUENZA: A SCOPING REVIEW - ROSYIDAH, DEVI U.; MUMTAZ, FAHMI D.; FARMA, AUFA F. F.; PUTRA, REYDOVAN; KHAIRUDDIN, HANIF N. (International Journal of Applied Pharmaceutics, 2025)
This scoping review evaluates the effectiveness of baloxavir, a cap-dependent endonuclease inhibitor, as an alternative antiviral treatment for influenza. A scoping review followed PRISMA guidelines, utilizing databases such as PubMed, SCOPUS, Science Direct, and cochrane to identify relevant studies published until November 2024. The review included 24 studies comparing baloxavir to placebo and other antiviral agents. It indicated that baloxavir significantly reduces the duration of influenza symptoms and has a favorable safety profile compared to oseltamivir and other neuraminidase inhibitors. Specifically, baloxavir demonstrated a shorter time to symptom relief and lower incidence of gastrointestinal side effects, particularly in younger populations. However, concerns regarding the emergence of viral variants that may impact treatment efficacy were noted. Overall, while baloxavir shows promise as an effective treatment option for influenza, further research across diverse populations is necessary to validate its global applicability and safety.